PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT EFARINA PANGKALAN KERINCI - Rahma, Dani; Jumiati, Sasmita; Rosnelly, Roesdi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
his research was conducted at Efarina Hospital Pangkalan Kerinci. The purposeof this study was to determine whether work motivation, work environment, andwork stress affect nurse performanceat Efarina Hospital Pangkalan Kerinci. Thepopulation in this study were all nurses at Efarina Hospital Pangkalan Kerinciwith a total of 76 employees. The sampling technique method uses a saturatedsample method, namely as many as 76 respondents. Technical analysis for testhypothesis that used in this study are double regression. using descriptivestatistical analysis and simple linear regression analysis to produce classicalassumption tests, data analysis models, coefficient of determination and provehypotheses. The of this study indicate that the variable of work motivation has apositive and significant effect on the performance of nurses, the work enviromentvariable has a positive and significant effect on the performance of nurses andwork stress has a negative and significant effect on the performance of nurses.Work motivation, work environment and work stress simultaneously affect theperformance of nurses. Keywords: Work Motivation; Work Environment; Work Stress; Performance